Finance and Development, March 2007. (Finance and Development; Finance and Development ;, 2007)
The Two Faces of Financial Globalization looks at the phenomenon of rising cross-border financial flows-credited with boosting growth in developing countries but also blamed for the emerging market crises of the late 1980s and 1990s. The lead article puts together a framework for analyzing studies about the costs and benefits of financial globalization. Other articles look at the worldwide allocation of capital, the role of finance in macroeconomic management, and changes in the investor base. "Picture This" illustrates the growth and direction of capital flows. One guest contributor describes India's capital account liberalization, and another looks at how participants in international finance can cope with a fluid financial landscape. "People in Economics" profiles Guillermo Calvo; "Back to Basics" explains the difference between the purchasing power parity exchange rate and market exchange rates as measures of global economic growth; and "Country Focus" spotlights Australia.